Transformasi Sumber Belajar untuk Meningkatkan Literasi Digital dan Kreativitas Mahasiswa Melalui Pembuatan Media Presentasi Power Point pada Mahasiswa Pendidikan Teknologi Informasi Universitas Nurul Hasanah Kutacane - Iswandi Walad; Wasni Maisarah; Chairunnisak; Ovielia Putri Rahman; Khairuddin Nasution (EduInovasi: Journal of Basic Educational Studies, 2025)
The transformation of learning resources at this time is very important for an effective and efficient teaching and learning process. Learning resources as a foundation and can also be said to be the main factor in the success of the learning process. The transformation of learning resources in accordance with the current digital era can facilitate the achievement of educational goals and also improve students' digital literacy. The purpose of this study is to determine the digital literacy and creativity of Information Technology Education students through the creation of power point presentation materials. The benefits of this study are so that students have a contribution to educational digital literacy, especially the creation of Power Point as presentation materials in the classroom. The method used in this study is descriptive qualitative. Qualitative methods are research methods based on the philosophy of positivism, used to examine the conditions of natural objects where researchers act as key instruments. The data collection techniques in this study are questionnaires and documentation. The questionnaire was made based on the 4P's Model by Kaufman & Sternberg, namely person, process, product, and press. This study uses data analysis techniques consisting of 3 flows of activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that through the transformation of learning resources can improve digital literacy and can also improve student creativity through technology that is developing very rapidly today, can be seen by producing a power point presentation media product so that it can become digital literacy while increasing student creativity and having a positive impact on the learning process.